Drifting on Alien Winds Exploring the Skies and Weather of Other Worlds - Carroll, Michael (Springer New York : Imprint: Springer, 2011)
Drifting on Alien Winds explores the bizarre weather of alien worlds, from the blistering hurricane-force winds of Venus to the gentle methane rain showers of Saturn's giant moon Titan. Blinding bolts of lightning sizzle through Jupiter's skies, ammonia blizzards swirl through Saturnian clouds, and Earth-sized cyclones pinwheel across Uranus and Neptune. Late-breaking scientific discoveries from spacecraft, observatories, and laboratories reveal the mysteries of weather across the Solar System. Our knowledge of weather on other worlds has not come easily. Drifting on Alien Winds introduces the inventors, engineers, and scientists who struggled to launch the first probes that would help us to understand the atmospheres of other worlds. The untold stories of early engineering feats and failures, from small Soviet Venus balloons to advanced studies of blimps and airplanes for Mars and Titan, are showcased here, along with what we've learned and are still trying to learn about alien skies. Some of today's most creative and scientifically feasible ideas for voyaging through distant skies are presented. With spectacular spacecraft images and stunning original paintings by the author, Drifting on Alien Winds is a feast for the eyes as well as the mind.